Restoration of Blood Pressure Control Through Management of Obstructive Sleep Apnea and Optimization of Testosterone Therapy in a Patient with Hypergonadotropic Hypogonadism - Shkvarok-Lisovenko, Anastasiia; Korost, Yaroslava (The Ukrainian Scientific Medical Youth Journal, 2026)
primary hypergonadotropic hypogonadism is an uncommon endocrine disorder resulting from primary testicular failure with preserved hypothalamic–pituitary regulation and requiring lifelong testosterone replacement therapy. In adult patients, this condition is frequently complicated by severe metabolic and cardiovascular disorders, particularly morbid obesity, arterial hypertension, and insulin resistance. The coexistence of these conditions significantly complicates both diagnostic evaluation and long-term therapeutic decision-making, especially when standard hormone replacement strategies fail to achieve stable biochemical and clinical control. To demonstrate the clinical significance of identifying and treating comorbid obstructive sleep apnea (OSA) syndrome as a prerequisite for effective testosterone replacement therapy and blood pressure control in a patient with hypergonadotropic hypogonadism and severe cardiometabolic comorbidities. A detailed clinical, laboratory, instrumental and follow-up assessment of a male patient with long-standing hypergonadotropic hypogonadism was performed, including endocrine, cardiological, and somnological evaluation. Therapeutic interventions and their outcomes were analyzed within a multidisciplinary management framework. We report the case of a 40-year-old male with a childhood diagnosis of primary hypergonadotropic hypogonadism who had been receiving long-term testosterone undecanoate therapy. Over time, the patient developed progressive morbid obesity (body mass index exceeding 50 kg/m²) accompanied by metabolic disturbances, which prevented sustained normalization of serum testosterone levels despite ongoing treatment. He presented with recurrent severe headaches, dizziness, transient visual impairment, tremor, and two episodes of short-term loss of consciousness. Clinical examination revealed persistent arterial hypertension with blood pressure values reaching 170/105 mmHg, corresponding to grade II hypertension and very high cardiovascular risk. Conventional antihypertensive therapy failed to achieve adequate blood pressure control. Extended diagnostic evaluation identified previously undiagnosed OSA, recognized as an independent contributor to hypertension and a relative contraindication to intensification of testosterone therapy. Initiation of continuous positive airway pressure (CPAP) therapy resulted in marked clinical improvement and enabled safe reassessment of testosterone replacement. Subsequent reduction of testosterone undecanoate injection intervals combined with adjunctive aromatase inhibitor therapy led to stable normalization of serum testosterone concentrations. This hormonal correction was associated with sustained blood pressure control below 130/85 mmHg without escalation of antihypertensive treatment and complete resolution of neurological symptoms. The achieved clinical stability persisted throughout follow-up. This clinical case highlights the complex and often underestimated interplay between hypergonadotropic hypogonadism, morbid obesity, OSA and arterial hypertension. It underscores the importance of a stepwise, pathophysiology-driven diagnostic approach, in which recognition and treatment of sleep-disordered breathing represent a critical prerequisite for the safe and effective optimization of testosterone replacement therapy. The case further emphasizes the necessity of a coordinated multidisciplinary strategy involving family physicians, endocrinologists, cardiologists, somnologists and andrologists to achieve sustainable clinical outcomes in patients with combined endocrine and cardiovascular comorbidities.